ANALISIS HUBUNGAN ANTARA ATRIBUT KUALITAS AUDIT DENGAN BIAYA EKUITAS MODAL (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2011) - Prasetyo Suparno, Denny; Kiswara, Endang (Diponegoro Journal of Accounting, 2013)
Audit This study aimed to analyze the relationship between audit quality attributes to the cost of equity capital. This study uses four variables : the cost of equity capital is proxired using the debt to equity rasio, the size ofthe public accounting firm, auditor industry specialization and audit tenure. This study used a sample of companies listed on the Indonesia Stock Exchange (IDX) 2009-2011. A total of 37companies in Indonesia that meet the criteria that have complete data for this study, which is expressed asa sample.This study uses quantitative methods and analysis methods usingpartial test using SPSS21.Test results of this study indicate that the size of the firm and audi ttenure is not significantly negatively related to the cost of equity capital. Auditor industry specialization and are not positively related significantly to the cost of equity capital. While testing conducted together all the variables on the cost of equity capitalis negatively related and does not significantly affect the cost of equity capital.